Interpretation of Fundamental Rights in Slovenia - Flander, Benjamin (Constitutional Reasoning and Constitutional Interpretation: Analysis on Certain Central European Countries, 2021)
This chapter introduces an analysis of the interpretation of fundamental rights in the practice of the Slovenian Constitutional Court and the European Court of Human Rights. A brief overview of the status and powers of the Constitutional Court is followed by a record of the common features of the constitutional adjudication and style of reasoning in fundamental rights cases. Then the application of fundamental rights will be analysed and the practice of interpreting them by the Slovenian Constitutional Court will be explored. In this main segment of our research we analysed 30 important cases of the last 10 years in which the Constitutional Court brought a final decision, and in which it made a substantive references to the judgements of either the European Court of Human Rights (ECtHR) or the European Court of Justice (ECJ). Among the selected cases, 19 decisions were issued in the constitutional complaint procedure and 11 decisions concern the review of the constitutionality of laws and other general acts, however in some decisions, these two types of constitutional judicial decision-making are both involved. The selected decisions refer to important aspects of the implementation of fundamental rights in the areas of criminal law and criminal procedure, civil law, administrative law, anti-discrimination law, family law, asylum law, European Union law and other areas of law. For different reasons, the majority of these decisions have been of outstanding relevance in Slovenia. The selected cases will be analysed according to the common methodology of the monograph, aimed at comparing the interpretation of fundamental rights in the case law of the constitutional courts of the countries of the Eastern Central European region, the ECtHR and the ECJ. Carefully scrutinizing them, we discovered that the Constitutional Court – while using different methods of legal interpretation – addressed a wide range of constitutional provisions and rights. The Constitutional Court’s interpretation of the constitutional provisions on fundamental rights contained in the selected decisions has had precedent effects on the legal order of the Republic of Slovenia. In substantive terms, in these cases, the Constitutional Court has taken a position on important aspects of the implementation of fundamental rights and determined their scope and limits. Furthermore, it has addressed the substantive meaning of important parts of the so-called constitutional material core (i.e., of principles of democracy, the rule of law and the separation of powers, of human dignity, personal liberty and privacy in a democratic state, etc.) and took decisions that have led to amendments in different areas of the Slovenian legal order.Following the analyses of the features of constitutional adjudication and reasoning in Slovenia, we will then proceed with exploring the judicial practice of the ECtHR and, to a much lesser extent, the ECJ, the two very important international courts. 28 cases of the ECtHR and 2 cases of the ECJ referenced by the Slovenian Constitutional Court will be scrutinised. The selected decisions of both international courts were considered on the merits in the decisions of Constitutional Court which were included in our study. Our survey in the section concerning ECtHR aims primarily at providing a record of the common features of the interpretation by the Court of fundamental rights enshrined in the European Convention on Human Rights (hereinafter Convention). We will try to determine main differences in the decision-making and reasoning style of the Slovenian Constitutional Court and the ECtHR, while the comparison with the adjudication practice of the ECJ and interpretation of the rights contained in the Charter of Fundamental Rights of the European Union is of lesser importance for this study.